Occurrence and spatial distribution of intestinal parasites in an agricultural center in Paraná State, Brazil - doi: 10.4025/actascihealthsci.v32i2.5283 (Acta Scientiarum. Health Sciences, 2010)
We determined the occurrence of human cases of intestinal parasites and their spatial distribution in an agricultural center of the state of Paraná in southern Brazil. Results from 5,219 stool examinations carried out in 2003 and 2004 in public and private clinical-pathology laboratories were analyzed. The overall occurrence of intestinal parasites was 19.8%. Entamoeba coli (7.2%) and Giardia duodenalis (5.2%) were the most frequent species. E. coli was present in 36.4%, G. duodenalis in 26.2% and E. nana in 13.6% of positive cases. According to spatial distribution, the highest occurrence of intestinal parasites was observed in the Piquiri/Guarujá area (p < 0.05), and the lowest in the CSU, Urupês and Paulista areas. In Piquiri/Guarujá, the most common species were G. duodenalis (22.2%) and E. coli (7.4%). Significant differences in the occurrence of enteroparasites were observed for females (p < 0.05) and children 0 to 10 years of age (p < 0.05). The occurrence of intestinal parasites in the municipality was mostly related to children, females, and residence in rural areas and the peripheries of urban centers, where the risk of infection is greater. This information will allow the development of appropriate measures for disease prevention and optimization of resources.